Preparation of capsule type composite phase change material

By using graphite modified polytetrafluoroethylene material to wrap the phase change material, the problem of low heat storage efficiency in the temperature range of 150-220℃ is solved, efficient heat storage and heat release are achieved, and thermal conductivity is improved. Thermal shock resistance has good application value.

CN119463812AActive Publication Date: 2025-02-18INNER MONGOLIA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411641910.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-18
Estimated Expiration
2044-11-18

AI Technical Summary

Technical Problem

The existing phase change heat storage materials have low heat storage efficiency in the temperature range of 150-220℃, and cannot effectively cover the temperature requirements of industrial heat and distributed solar organic Rankine cycles.

Method used

The graphite modified polytetrafluoroethylene material with high temperature resistance, corrosion resistance and good thermal conductivity is used as the carrier, and the phase change material is wrapped through its microstructure characteristics to prepare a composite phase change with high heat storage ability and good thermal shock resistance. Heat storage material.

Benefits of technology

It achieves efficient heat storage and heat release within the temperature range of 150-220℃, improves thermal conductivity and thermal shock resistance, reduces costs, facilitates large-scale production, and has good application value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463812A_ABST
    Figure CN119463812A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a capsule type composite phase change material, and belongs to the technical field of heat transfer and storage. The capsule type composite phase change material is composed of a phase change material core material and a graphite modified polytetrafluoroethylene wall material coating the outer layer of the phase change material core material. According to the invention, the graphite modified polytetrafluoroethylene material with high temperature resistance, corrosion resistance and good heat-conducting property is used as a carrier, and the phase-change material is wrapped by utilizing the microstructure characteristics of the graphite modified polytetrafluoroethylene material, so that the composite phase-change heat storage material with high heat storage capacity, good thermal shock resistance, high heat conductivity and small reversible heat charge / heat release corrosion is prepared; and the cost is low, large-scale production is facilitated, and the application value is very good. Through graphite modification of polytetrafluoroethylene, the heat-conducting property and the mechanical property of the composite material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat transfer and heat storage, and in particular to a method for preparing a capsule-type composite phase change material. Background Art

[0002] Phase change materials (PCM) play a key role in the field of phase change heat storage due to their high heat storage efficiency, stable chemical properties, and low cost. At present, the phase change temperatures of various phase change heat storage materials are generally below 150°C or above 220°C. However, the temperatures of industrial heat and distributed solar organic Rankine cycles are mostly concentrated in the temperature range of 150-220°C. Existing phase change heat storage materials cannot cover this range well, and further research is still needed.

[0003] In order to make up for the lack of high-performance phase change thermal storage materials between 150-220℃, molten salt composite thermal storage materials are one of the research directions. Molten salt composite thermal storage materials are materials that use the phase change characteristics of molten salt to store and release heat; molten salt is an ionic melt composed of cations and anions formed after the melting of salts. It has the advantages of high heat storage density, low viscosity, low cost, long life, and high efficiency. It can be used in the field of heat transfer and heat storage. Molten salt composite thermal storage materials can be prepared into the structure of phase change capsules with solar salt, Hitec salt, modified solar salt, etc. as phase change material core materials, polytetrafluoroethylene, silica, etc. as wall materials. However, the existing molten salt composite thermal storage materials in the form of phase change capsule structure usually have problems such as low shell thermal conductivity and poor thermal properties, which limit their application in heat recovery. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a capsule-type composite phase change material to solve the above-mentioned problems in the background technology. The present invention uses a graphite-modified polytetrafluoroethylene material that is resistant to high temperature, corrosion-resistant, and has good thermal conductivity as a carrier, and uses its own microstructural characteristics to wrap the phase change material, thereby preparing a composite phase change heat storage material with high heat storage capacity, good thermal shock resistance, high thermal conductivity, and low heat charging / heat release reversible corrosion. It is low-cost, easy to mass produce, and has good application value. By modifying the graphite of polytetrafluoroethylene, the thermal conductivity and mechanical properties of the composite material are improved.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is to provide a capsule-type composite phase change material, which is composed of a phase change material core material and a graphite-modified polytetrafluoroethylene wall material coated on the outer layer of the phase change material core material.

[0007] The second technical solution of the present invention is to provide a method for preparing the above-mentioned capsule-type composite phase change material, comprising the following steps:

[0008] (1) taking phase change material powder and pressing it into shape to obtain a phase change material core material;

[0009] Mixing polytetrafluoroethylene powder and graphite powder to obtain modified polytetrafluoroethylene powder;

[0010] (2) wrapping the modified polytetrafluoroethylene powder on the surface of the phase change material core material and compacting it to obtain a phase change capsule embryo;

[0011] (3) The phase change capsule blank is subjected to a thermoforming treatment to obtain the capsule-type composite phase change material.

[0012] Preferably, the phase change material powder is a mixed nitrate powder with a melting point of 150-220°C.

[0013] Preferably, the mold used for the compression molding is a spherical mold cavity or a cylindrical mold cavity.

[0014] Preferably, the compression molding pressure is 1200N, and the density of the phase change material core obtained is 1809-1949kg / m 3 .

[0015] More preferably, the preparation method of the mixed nitrate powder with a melting point of 150-220°C is: heating the mixed nitrate powder to a molten state, cooling it, then taking it out, and crushing it to an average particle size of 75 μm to obtain the mixed nitrate powder with a melting point of 150-220°C.

[0016] More preferably, the mixed nitrate powder contains KNO 3 、NaNO 3 、NaNO 2 and Ca(NO 3 ) 2 Two or more of the above.

[0017] Preferably, the mass ratio of the polytetrafluoroethylene powder to the graphite powder is 10:1.

[0018] Preferably, the mass ratio of the phase change material core to the modified polytetrafluoroethylene powder is 6.5-7:2.5-3.

[0019] Preferably, the compaction pressure is 1200N, and the density of the obtained phase change capsule is 1988-2385kg / m 3 .

[0020] Preferably, the thermoforming process is: heating the phase change capsule blank at 350° C. for 15 min, then heating at 450° C. for 15 min, and finally cooling to 350° C. and heating for 15 min.

[0021] In the thermoforming process of the present invention, the polytetrafluoroethylene of the outermost layer of the phase change capsule embryo first begins to soften and partially melt at 350°C, which provides assistance for subsequent molding; after the temperature is raised to 450°C, the melting and flow of the polytetrafluoroethylene can be further promoted, so that it can be better filled; when the temperature is lowered to 350°C, the cooling process of the reaction system can be controlled, so that the molten polytetrafluoroethylene is gradually solidified and stabilized, and it is also helpful to eliminate the internal stress of the product and improve the crystallinity of the product.

[0022] The third technical solution of the present invention is to provide an application of the above-mentioned capsule-type composite phase change material in the field of phase change heat storage.

[0023] The present invention presses the phase change material powder into a shape, and then presses a layer of modified polytetrafluoroethylene (PTFE) powder thereon to obtain the final product. When the capsule-type composite phase change material is heated, the air in the capsule is discharged through the micropores on the surface of the PTFE shell layer, and the volume expansion of the phase change material causes the PTFE to expand synchronously. In addition, the solidification of the molten PCM starts from the wall surface first, and the PTFE shell layer can maintain the same volume due to the support of the solid PCM that solidifies first, while the volume of the PCM decreases after solidification, so a certain volume of cavity is formed in the capsule, which can optimize heat transfer, control the temperature distribution of the phase change material, and improve the overall efficiency and performance of the phase change capsule.

[0024] The beneficial technical effects of the present invention are as follows:

[0025] The present invention uses graphite-modified polytetrafluoroethylene material with high temperature resistance, corrosion resistance and good thermal conductivity as a carrier, and uses its own microstructural characteristics to wrap the phase change material, thereby preparing a composite phase change heat storage material with high heat storage capacity, good thermal shock resistance, high thermal conductivity, and small reversible corrosion of heat charging / heat release, and the material has low cost, is easy to mass produce, and has good application value. By modifying the graphite of polytetrafluoroethylene, the thermal conductivity and mechanical properties of the composite material are improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1The thermal properties test results of different types of phase change material core materials in Example 1. Among them, (a) is the melting point, (b) is the latent heat of melting, (c) is the specific heat capacity, (d) is the thermal conductivity, (e) is the density, and (f) is the viscosity.

[0028] Figure 2 These are the measurement results of the decomposition points of different types of phase change material core materials in Example 1.

[0029] Figure 3 The microscopic morphology of the products of Example 1 and Comparative Examples 1-2 are shown in FIG. 1 , wherein (a) is PTFE, (b) is graphite-PTFE, (c) is polyphenylene ester-PTFE, (d) is carbon fiber-PTFE, (e) is copper powder-PTFE, and (f) is molybdenum disulfide-PTFE.

[0030] Figure 4 Infrared spectra of PTFE, graphite-PTFE, and polyphenylene-PTFE.

[0031] Figure 5 These are the infrared spectra of carbon fiber-PTFE, copper powder-PTFE, and molybdenum disulfide-PTFE.

[0032] Figure 6 These are the XRD patterns of PTFE, graphite-PTFE, and polyphenylene-PTFE.

[0033] Figure 7 These are the XRD patterns of carbon fiber-PTFE, copper powder-PTFE, and molybdenum disulfide-PTFE. DETAILED DESCRIPTION

[0034] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0035] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0037] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0038] Unless otherwise specified, the "room temperature" in the present invention is 10-30°C.

[0039] The raw material composition and proportion of the phase change material powder (1S, 2S, 3S, 1H, 2H, solar salt) used in the following embodiments and comparative examples of the present invention are shown in Table 1. The preparation method of the phase change material powder used is: heating the mixed nitrate powder to a molten state, cooling it, then taking it out, and crushing it to an average particle size of 75 μm to obtain a phase change material powder.

[0040] Table 1 Raw material composition and proportion

[0041]

[0042]

[0043] The average particle size of the graphite powder used in the present invention is 10 μm, the average particle size of the polyphenylene ester powder is 10 μm, the average diameter of the carbon fiber is 10 μm, the average particle size of the copper powder is 10 μm, and the average particle size of the molybdenum disulfide powder is 10 μm. The raw materials used in the following embodiments and comparative examples of the present invention are all commercially available products.

[0044] Example 1

[0045] The preparation of capsule-type composite phase change material is carried out by using 1S, 2S, 3S, 1H, 2H or solar salt as phase change material powder respectively, and the steps are as follows:

[0046] (1) Take the phase change material powder, put it into a spherical mold cavity with a diameter of 19 mm, and use a hydraulic press to press and mold it to obtain the phase change material core material (pressure is 1200N, the density of the phase change material core material is 1925kg / m 3 );

[0047] The polytetrafluoroethylene powder and the graphite powder are mixed in a mass ratio of 10:1 to obtain a modified polytetrafluoroethylene powder;

[0048] (2) Prepare a phase change material core material and modified polytetrafluoroethylene powder in a mass ratio of 5.875:2.44, evenly wrap the modified polytetrafluoroethylene powder on the surface of the phase change material core material, put it into a spherical mold cavity, and compact it using a hydraulic press to obtain a phase change capsule embryo (pressure is 1200N, and the density of the phase change capsule embryo is 2150kg / m 3 );

[0049] (3) The phase change capsule embryo is subjected to thermoforming treatment; the phase change capsule embryo is first heated at 350°C for 15 minutes, then heated at 450°C for 15 minutes, and finally cooled to 350°C and heated for 15 minutes, and then naturally cooled to room temperature to obtain a capsule-type composite phase change material (the product prepared with 3s as the phase change material powder is recorded as graphite-PTFE).

[0050] Example 2

[0051] The only difference from graphite-PTFE is that the mold shape during hydraulic pressing is modified to a cylindrical cavity with a diameter of 15m.

[0052] Comparative Example 1

[0053] The only difference from graphite-PTFE is that the graphite powder in step (1) is changed to an equal mass of polyphenylene ester powder, carbon fiber, copper powder or molybdenum disulfide powder, and the obtained products are recorded as polyphenylene ester-PTFE, carbon fiber-PTFE, copper powder-PTFE, and molybdenum disulfide-PTFE.

[0054] Comparative Example 2

[0055] The only difference from Example 1 is that the addition of graphite powder in step (1) is omitted, and the obtained product is recorded as PTFE.

[0056] Effect verification

[0057] The thermal properties of the different types of phase change material cores prepared in Example 1 were tested. Figure 1-2 As shown in Table 2-3.

[0058] Table 2 Thermophysical properties parameters

[0059] Thermophysical parameters Solar Salt <![CDATA[Density (kg / m 3 )]]> 1925 Latent heat (J / kg) 96060 Specific heat capacity (J / (kg·K)) 1520 Thermal conductivity (W / (m·K)) 0.45(l)0.75(s) Dynamic viscosity (Pa·s) 0.00693 Thermal expansion coefficient (1 / K) 0.000375 Solid phase temperature (K) 493.35 Liquidus temperature(K) 518.45

[0060] Table 3 Thermophysical properties parameters

[0061]

[0062]

[0063] Figure 1 The thermal properties test results of different types of phase change material core materials in Example 1. Among them, (a) is the melting point, (b) is the latent heat of melting, (c) is the specific heat capacity, (d) is the thermal conductivity, (e) is the density, and (f) is the viscosity.

[0064] Figure 1 The solar salt, 1s, 2s, 3s, 1h and 2h in the reference refer to the relevant data of the phase change material core materials obtained with solar salt, 1s, 2s, 3s, 1h and 2h as raw materials.

[0065] Figure 2 These are the measurement results of the decomposition points of different types of phase change material core materials in Example 1.

[0066] Figure 2 The 1S, 2S, 3S, 1H and 2H in the table refer to the relevant data of the phase change material core material obtained with 1S, 2S, 3S, 1H and 2H as raw materials respectively.

[0067] Figure 3 The microscopic morphology of the products of Example 1 and Comparative Examples 1-2 are shown in FIG. 1 , wherein (a) is PTFE, (b) is graphite-PTFE, (c) is polyphenylene ester-PTFE, (d) is carbon fiber-PTFE, (e) is copper powder-PTFE, and (f) is molybdenum disulfide-PTFE.

[0068] Prepare infrared spectrum data, analyze the information of chemical bonds and functional groups in the experimental sample according to the infrared spectrum, and determine the chemical structure and identification of the experimental sample by comparing the infrared spectrum with the infrared spectrum of other samples with known structures. Figure 4-5 shown.

[0069] Figure 4 Infrared spectra of PTFE, graphite-PTFE, and polyphenylene-PTFE.

[0070] Figure 5 These are the infrared spectra of carbon fiber-PTFE, copper powder-PTFE, and molybdenum disulfide-PTFE.

[0071] Figure 6 These are the XRD patterns of PTFE, graphite-PTFE, and polyphenylene-PTFE.

[0072] Figure 7 These are the XRD patterns of carbon fiber-PTFE, copper powder-PTFE, and molybdenum disulfide-PTFE.

[0073] Table 4 Thermophysical properties parameters

[0074]

[0075]

[0076] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A capsule-type composite phase change material, characterized in that: The invention is composed of a phase change material core material and a graphite modified polytetrafluoroethylene wall material coated on the outer layer of the phase change material core material.

2. A method for preparing the capsule-type composite phase change material according to claim 1, characterized in that: The following steps are involved: (1) taking phase change material powder and pressing it into shape to obtain a phase change material core material; Mixing polytetrafluoroethylene powder and graphite powder to obtain modified polytetrafluoroethylene powder; (2) wrapping the modified polytetrafluoroethylene powder on the surface of the phase change material core material and compacting it to obtain a phase change capsule embryo; (3) The phase change capsule blank is subjected to a thermoforming treatment to obtain the capsule-type composite phase change material.

3. The preparation method according to claim 2, characterized in that: The phase change material powder is a mixed nitrate powder with a melting point of 150-220°C.

4. The preparation method according to claim 2, characterized in that: The compression molding pressure is 1200N, and the density of the phase change material core obtained is 1809-1949kg / m 3 .

5. The preparation method according to claim 2, characterized in that: The mass ratio of the polytetrafluoroethylene powder to the graphite powder is 10:

1.

6. The preparation method according to claim 2, characterized in that: The mass ratio of the phase change material core material to the modified polytetrafluoroethylene powder is 6.5-7:2.5-3.

7. The preparation method according to claim 2, characterized in that: The compaction pressure is 1200N, and the density of the obtained phase change capsule is 1988-2385kg / m 3 .

8. The preparation method according to claim 2, characterized in that: The thermoforming process is as follows: heating the phase change capsule blank at 350° C. for 15 minutes, then heating at 450° C. for 15 minutes, and finally cooling to 350° C. and heating for 15 minutes.

9. Use of the capsule-type composite phase change material according to claim 1 in the field of phase change heat storage.

Citation Information

Patent Citations

  • Core-shell structure composite phase change energy storage material and preparation method thereof

    CN106281234A

  • Graphene-silicon dioxide composite wall-material phase-change nanocapsule and preparation method thereof

    CN108774499A

  • Heat conduction composite material and preparation method thereof

    CN111909516A

  • Preparation method of molten salt nanometer phase change heat storage material at high decomposition temperature

    CN117887424A